(untitled) (Conferencea, 2024)
This article provides a comprehensive analysis of the theoretical foundations, psychological-pedagogical aspects, and practical significance of teaching students based on national content. In modern education, the integration of national heritage and culture into the learning process is becoming crucial in the context of globalization, as it contributes to preserving national identity and fostering qualities such as patriotism and social responsibility among learners. The article explores the definition of national content, its functional role in education, pedagogical-psychological bases, advantages, limitations, and strategic approaches to its application in Uzbekistan’s education system. The research aims to develop innovative methods to enhance the quality of education through the utilization of Uzbekistan’s rich cultural heritage.